High dose folic acid is a potential treatment for pulmonary hypertension, including when associated with COVID-19 pneumonia. (October 2020) - Wiltshire, Esko; Peña, Alexia Sophie; MacKenzie, Karen; Shaw, Geoffrey; Couper, Jennifer
Abstract: Background: Pulmonary hypertension is a significant complication for some patients with COVID-19 pneumonia, especially those requiring intensive care. Tachyphylaxis to the current therapy, inhaled nitric oxide (iNO), is also common. In vitro, folic acid directly increases nitric oxide (NO) production and extends its duration of action; effects which could be of benefit in reversing pulmonary hypertension and severe hypoxaemia. Our work has shown that, in the systemic circulation, folic acid in high dose rapidly improves nitric oxide mediated vasodilation, by activating endothelial nitric oxide synthase (eNOS). Hypothesis: A similar effect of high dose folic acid on pulmonary endothelial function would be expected from the same mechanism and would lead to improvement in pulmonary perfusion. We therefore hypothesise that folic acid, 5 mg or greater, is a useful therapeutic option for pulmonary hypertension and/or refractory severe hypoxaemia, in patients with severe COVID-19 associated pneumonia in whom NO therapy is considered, with a very low risk of adverse effects.